Characterization of the Climate Absolute Radiance and Refractivity Observatory (CLARREO) ability to serve as an infrared satellite intercalibration reference. Issue 8 (22nd April 2016) - Tobin, David; Holz, Robert; Nagle, Fred; Revercomb, Henry
Abstract: Climate Absolute Radiance and Refractivity Observatory (CLARREO) is a future mission employing an infrared spectrometer with unprecedented calibration accuracy and the ability to assess its calibration on‐orbit using a novel verification system. Utilizing this capability for satellite intercalibration is a primary objective of the mission. This paper presents a new infrared intercalibration methodology that minimizes the intercalibration uncertainties and provides uncertainty estimates resulting from the scene variability and instrument noise. Results of a simulation study to characterize realistic spatial and temporal matching differences for simultaneous nadir overpasses (SNOs) of CLARREO and existing hyperspectral sounders are presented. This study, along with experience with intercalibration of real data, finds that intercalibration uncertainties are minimized when the SNOs are not screened for sky conditions but instead weighted based on the observed scene variability. Intercalibration performance is investigated for a 90° polar orbit mission and for a Pathfinder mission on the International Space Station, for various potential CLARREO footprint sizes, and as a function of mission length, scene brightness temperature, and wavelength. The results are encouraging and suggest that biases between CLARREO and sounder observations can be determined with low uncertainty and with high time frequency during a CLARREO mission. For example, the simulations suggest that a CLARREO footprint of 50 to 100 km in diameter is optimal for intercalibration, and that the 3 sigma intercalibration uncertainty is less than 0.1 K for channels at infrared window wavelengths using 2 months of accumulated SNOs, and for more absorbing channels with less scene variability the uncertainties are less than 50 mK. Key Points: CLARREO will be able to serve as a reference for infrared satellite intercalibration CLARREO intercalibration is characterized for various potential orbits and other key parameters Intercalibration uncertainty of 0.1 K is reached after accumulating several months of colocated data